2018
DOI: 10.1002/rmv.2011
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infection in day care centres: A systematic review and meta‐analysis of prevalence of infection in children

Abstract: Summary Maternofetal transmission of cytomegalovirus (CMV) is the most common infectious cause of congenital malformation in developed countries. Maternal infection often results from close contact with infected children, and this may occur in day care centres (DCCs). A systematic review of observational studies was conducted to examine the prevalence of CMV infection among children attending DCCs. Meta‐analysis using the random effect model was performed for studies including controls. Sources included PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 61 publications
0
20
0
1
Order By: Relevance
“…EBV infection is primarily transmitted via saliva and is nearly universal, acquired during early childhood in developing countries and before reaching young adulthood in developed countries [6][7][8]. During primary infection, EBV is thought first to infect oral epithelial cells overlying the lymphoid tissue known as Waldeyer's ring [9].…”
Section: Introductionmentioning
confidence: 99%
“…EBV infection is primarily transmitted via saliva and is nearly universal, acquired during early childhood in developing countries and before reaching young adulthood in developed countries [6][7][8]. During primary infection, EBV is thought first to infect oral epithelial cells overlying the lymphoid tissue known as Waldeyer's ring [9].…”
Section: Introductionmentioning
confidence: 99%
“…Parents with a child 1 to 2 years of age in day care are at particularly high risk of encountering CMV infection. 12,13 A recent study from France found that 3% of women who were CMV negative in their first pregnancy, seroconverted in the periconceptual period or first trimester of their next pregnancy. 14 Many women of reproductive age (45% to 100%) have had CMV infection prior to pregnancy.…”
Section: How Does CMV Infection Maternal-fetal Transmission and Fmentioning
confidence: 99%
“…Infection in children in day care is common, and children may excrete infectious virus for long periods. Parents with a child 1 to 2 years of age in day care are at particularly high risk of encountering CMV infection 12,13 . A recent study from France found that 3% of women who were CMV negative in their first pregnancy, seroconverted in the periconceptual period or first trimester of their next pregnancy 14 .…”
Section: How Does CMV Infection Maternal‐fetal Transmission and Fetmentioning
confidence: 99%
See 1 more Smart Citation
“…Human cytomegalovirus (CMV) is the leading non-genetic cause of congenital malformation in developed countries including Australia. 8,9 Infection may result in fetal and neonatal death or the development of serious clinical sequelae including sensorineural hearing loss and neurodevelopmental disability. We have recently shown that awareness in the medical and general community about congenital CMV is very low and in need of improvement.…”
Section: Congenital Cytomegalovirus Infection (Cmv)mentioning
confidence: 99%